From Green to REDD, from Aid to Trade: Translating the Forest Carbon Concept into Practice - Pokharel, Bharat; Baral, Jagadish (Journal of Forest and Livelihood, 2009)
This paper summarizes the Reducing Emissions from Deforestation and Degradation (REDD) concept in terms of its four objectives and then discusses necessary strategies for achieving these objectives in Nepal. It identifies the main challenges for the country in engaging in the World Bank-supported REDD readiness processes. It concludes that, in order to achieve the potential benefits, the REDD process needs to be ‘Nepalized'. This means developing a participatory and adaptive learning process among a wide range of stakeholders as an alternative to th blueprint approach, which is perhaps envisaged by the World Bank. The authors argue that Nepal's governance systems are not particularly amenable to collaborative learning process, and conclude that several challenges need to be overcome before the REDD process can be put into practice. A primary benefit of addressing these challenges would be the strengthening of Nepal's position to trade in carbon, rather than as a recipient of development aid. Key words: REDD, forest carbon, carbon trade, development aid, multi-stakeholder processes Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.37-40